Starting Statistics : a Short, Clear Guide. - Burdess, Neil (Sage Publications, 2010)
Statistics: A Short, Clear Guide is an accessible, humorous and easy introduction to statistics for social science students. In this refreshing book, experienced author and academic Neil Burdess shows that statistics are not the result of some mysterious black magic", but rather the result of some very basic arithmetic. Getting rid of confusing x's and y's, he shows that it's the intellectual questions that come before and after the calculations that are important: (i) What are the best statistics to use with your data? and (ii) What do the calculated statistics tell you? Statistics: A Sh.